Manajemen Humas Digital dalam Pendidikan Khusus: Strategi dan Tantangan Membangun Citra Sekolah melalui Media Sosial - Solehah, Siti; Ginanto, Dion Eprijum; Atika, Atika (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to comprehensively examine public relations (PR) strategies in building and strengthening a positive institutional image through the optimization of social media at Special School (SLB) Prof. Dr. Sri Soedewi Masjchun Sofwan, S.H. Jambi. Employing a qualitative descriptive approach, the research focuses on PR strategic practices in responding to communication transformation in the digital era. The utilization of social media platforms such as Instagram, TikTok, Facebook, and YouTube has reshaped communication patterns into more open, interactive, and professional forms. The findings reveal that PR strategies are implemented through four primary roles: as a communicator, a relationship builder, a management support function (back-up management), and an image creator (good image maker). These roles significantly contribute to enhancing public trust and strengthening institutional reputation. This study is expected to contribute both theoretically and practically to the development of public relations strategies, particularly within special education institutions in the digital era.